2017
DOI: 10.1158/0008-5472.can-16-2589
|View full text |Cite
|
Sign up to set email alerts
|

Krüppel-like Transcription Factor KLF10 Suppresses TGFβ-Induced Epithelial-to-Mesenchymal Transition via a Negative Feedback Mechanism

Abstract: TGFβ-SMAD signaling exerts a contextual effect that suppresses malignant growth early in epithelial tumorigenesis but promotes metastasis at later stages. Longstanding challenges in resolving this functional dichotomy may uncover new strategies to treat advanced carcinomas. The Krüppel-like transcription factor KLF10 is a pivotal effector of TGFβ/SMAD signaling that mediates anti-proliferative effects of TGFβ. In this study, we show how KLF10 opposes the pro-metastatic effects of TGFβ by limiting its ability t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
57
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(61 citation statements)
references
References 56 publications
4
57
0
Order By: Relevance
“…21 KLF10 was also identified as an anti-metastasis gene by the inhibition of Slug gene transcription. 22 In our study, functional assays revealed that KLF10 inhibited the migration and invasion of BCa cell lines ( Figures 6C and 6D).…”
Section: Mir-570-3p Promotes Migration and Invasion Of Bca Cell Linessupporting
confidence: 54%
See 1 more Smart Citation
“…21 KLF10 was also identified as an anti-metastasis gene by the inhibition of Slug gene transcription. 22 In our study, functional assays revealed that KLF10 inhibited the migration and invasion of BCa cell lines ( Figures 6C and 6D).…”
Section: Mir-570-3p Promotes Migration and Invasion Of Bca Cell Linessupporting
confidence: 54%
“…Transcript factor KLF10 was characterized as a tumor-suppressor gene in cancers. 21,22 Metastatic brain tumors from lung adenocarcinoma indicated that KLF10 was at an abnormally low level in brain tumors. 21 KLF10 was also identified as an anti-metastasis gene by the inhibition of Slug gene transcription.…”
Section: Mir-570-3p Promotes Migration and Invasion Of Bca Cell Linesmentioning
confidence: 99%
“…It has been shown that tumour cells have a higher propensity to secrete larger quantity of exosome 67,68 ; for instance, cancer-associated fibroblasts (CAFs) support tumour cells in proliferation, delaying senescence and resisting against drugs, which induced by exosome-secreted miR-9 and the human telomerase reverse transcriptase (hTERT). 69,70 Activation of signalling pathways by exosomes is one of the way to modulate the tumour microenvironment, such as irritation of the TGF-β/Smad pathway by transferring TGF-β to human umbilical cord-derived mesenchymal cells (hucMSCs), subsequently differentiating into CAFs. 71 Moreover, recent research shows that transferring TGF-β also contributes fibroblasts converse to myofibroblasts, which could secrete insulin-like growth factor 1 (IGF-1), activin A and VEGF to induce tumour progression.…”
Section: Modul Ation Of the Tumour Microenvironmentmentioning
confidence: 99%
“…During EMT, down-regulation of E-cadherin leads to the loss of cell adhesion, upregulation of Vimentin and N-cadherin causes the reorganization of the actin cytoskeleton and promotes the motility [5], and upregulation of transcription factors such as Snail, Slug and Twist induces EMT [6]. In addition, TGF-β/SMADs [7], PI3K/Akt [8] and other signaling pathways were participated in regulating EMT. In our previous study, we have found that β-arrestin1 had a higher expression in lung metastases than in primary CRC.…”
Section: Introductionmentioning
confidence: 99%